Diabetes Mellitus Promotes the Development of Atherosclerosis: The Role of NLRP3 - Ye, Jingxue; Li, Lanfang; Wang, Min; Ma, Qiuxiao; Tian, Yu; Zhang, Qiong; Liu, Jiushi; Li, Bin; Zhang, Bengang; Liu, Haitao; Sun, Guibo (Frontiers in Immunology, 2022)
Atherosclerosis is one of the main complications of diabetes mellitus, involving a variety of pathogenic factors. Endothelial dysfunction, inflammation, and oxidative stress are hallmarks of diabetes mellitus and atherosclerosis. Although the ability of diabetes to promote atherosclerosis has been demonstrated, a deeper understanding of the underlying biological mechanisms is critical to identifying new targets. NLRP3 plays an important role in both diabetes and atherosclerosis. While the diversity of its activation modes is one of the underlying causes of complex effects in the progression of diabetes and atherosclerosis, it also provides many new insights for targeted interventions in metabolic diseases.